Does International Child Sponsorship Work? A Six-Country Study of Impacts on Adult Life Outcomes - Wydick, Bruce; Glewwe, Paul; Rutledge, Laine (Journal of Political Economy, 2013)
Child sponsorship is a leading form of direct aid from wealthy country households to children in developing countries. Over 9 million children are supported through international sponsorship organizations. Using data from six countries, we estimate impacts on several outcomes from sponsorship through Compassion International, a leading child sponsorship organization. To identify program effects, we utilize an age-eligibility rule implemented when programs began in new villages. We find large, statistically significant impacts on years of schooling; primary, secondary, and tertiary school completion; and the probability and quality of employment. Early evidence suggests that these impacts are due, in part, to increases in children’s aspirations.